Induction and Inhibition of Type I Interferon Responses by Distinct Components of Lymphocytic Choriomeningitis Virus - Zhou, Shenghua (American Society for Microbiology (ASM), 2010)
Type I interferons (IFNs) play a critical role in the host defense against viruses. Lymphocytic choriomeningitis virus (LCMV) infection induces robust type I IFN production in its natural host, the mouse. However, the mechanisms underlying the induction of type I IFNs in response to LCMV infection have not yet been clearly defined. In the present study, we demonstrate that IRF7 is required for both the early phase (day 1 postinfection) and the late phase (day 2 postinfection) of the type I IFN response to LCMV, and melanoma differentiation-associated gene 5 (MDA5)/mitochondrial antiviral signaling protein (MAVS) signaling is crucial for the late phase of the type I IFN response to LCMV. We further demonstrate that LCMV genomic RNA itself (without other LCMV components) is able to induce type I IFN responses in various cell types by activation of the RNA helicases retinoic acid-inducible gene I (RIG-I) and MDA5. We also show that expression of the LCMV nucleoprotein (NP) inhibits the type I IFN response induced by LCMV RNA and other RIG-I/MDA5 ligands. These virus-host interactions may play important roles in the pathogeneses of LCMV and other human arenavirus diseases.